2005
DOI: 10.1196/annals.1282.003
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Rat INSL3 Receptor

Abstract: Human LGR8, initially discovered as a low-affinity relaxin receptor, has now been characterized as the INSL3 receptor. To investigate LGR8 function in the rat, an LGR8 ortholog was identified in the rat genome, and the full-length sequence was cloned and expressed. Rat LGR8 bound INSL3 with high affinity, clearly demonstrating that it is the rat INSL3 receptor. Interestingly, native rat relaxin did not activate rat LGR8, indicating that relaxin is not an endogenous ligand for rat LGR8. LGR8 mRNA expression was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 7 publications
1
46
1
1
Order By: Relevance
“…As discussed earlier, porcine relaxin activates both LGR7 and LGR8 from human, rat or mouse sources. But recent evidence suggests that mouse or rat relaxin activates only LGR7 in these species [25]. This was further illustrated by the inability of mouse relaxin to rescue the failed testicular descent in the InsL3-null mouse [26], and thus in the rodent, InsL3 alone is responsible for activation of LGR8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed earlier, porcine relaxin activates both LGR7 and LGR8 from human, rat or mouse sources. But recent evidence suggests that mouse or rat relaxin activates only LGR7 in these species [25]. This was further illustrated by the inability of mouse relaxin to rescue the failed testicular descent in the InsL3-null mouse [26], and thus in the rodent, InsL3 alone is responsible for activation of LGR8.…”
Section: Discussionmentioning
confidence: 99%
“…This was further illustrated by the inability of mouse relaxin to rescue the failed testicular descent in the InsL3-null mouse [26], and thus in the rodent, InsL3 alone is responsible for activation of LGR8. One study has suggested that human relaxin-3 may activate rat LGR8 [25], and therefore it is possible that the increased cAMP in HSC exposed to porcine relaxin, or human InsL3 and relaxin-3, may be due to activation of LGR8.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in gubernacular cells or osteoblasts , activation of RXFP2 causes increased cAMP, but in male germ cells and oocytes, decreased cAMP is observed (Kawamura et al, 2004), perhaps reflecting expression patterns of signaling proteins in different cells (Halls et al, 2009a). Although the relaxins of some species activate RXFP2 in vitro Kumagai et al, 2002;Scott et al, 2005a;Bathgate et al, 2006b), there is no evidence that relaxin activates RXFP2 in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…1A ). Secondly, sections hybridized with the three individual oligonucleotide probes displayed the same distribution of labelling (data not shown), and finally the oligonucleotide probes used produced strong, specific labelling of sections of gubernaculum from a 17-day rat embryo and adult testis (data not shown; Scott et al 2005). Microscopic analysis of high-resolution nuclear emulsion autoradiograms from counterstained kidney sections indicated that Lgr8 mRNA expression was restricted to putative mesangial cells within the adult glomeruli (Fig.…”
Section: Detection Of Regional and Cellular Lgr8 Mrna Expression In Amentioning
confidence: 76%
“…In preliminary studies, rat Lgr8 gene was cloned and sequenced (see Scott et al 2005) and subsequently its distribution in different rat tissues was explored by RT-PCR. Briefly, sequences homologous to regions of the human LGR8 cDNA were identified in bacterial artificial chromosome clones in the NCBI HTGS database.…”
Section: Cloning Sequencing and Tissue Distribution Of Rat Lgr8mentioning
confidence: 99%